Harnessing Chaos The Bible in English Political Discourse Since 1968 - Crossley, James G. (The Library of New Testament Studies, 2016)
"Harnessing Chaos" is an explanation of changes in dominant politicalized assumptions about what the Bible really means in English culture since the 1960s. James G. Crossley looks at how the social upheavals of the 1960s, and the economic shift from the post-war dominance of Keynesianism to the post-1970s dominance of neoliberalism, brought about certain emphases and nuances in the ways in which the Bible is popularly understood, particularly in relation to dominant political ideas. This book examines the decline of politically radical biblical interpretation in parliamentary politics and the victory of (a modified form of) Margaret Thatcher's re-reading of the liberal Bible tradition, following the normalisation of (a modified form of) Thatcherism more generally.